Vitamin D treatment attenuates 2,4,6-trinitrobenzene sulphonic acid (TNBS)-induced colitis but not oxazolone-induced colitis - Liu, Tianjing (Sci Rep, 2016)
Crohn’s disease (CD) and ulcerative colitis (UC) have different immunological mechanisms, while both of them are potential targets of vitamin D treatment. In this study, we have tried to address the role of vitamin D in CD and UC using two mouse models. Mice of C57B6L were given vitamin D before the induction of colitis. Our results showed that vitamin D attenuated 2,4,6-trinitrobenzene sulphonic acid (TNBS)-induced colitis but not oxazolone-induced colitis. Vitamin D could preserve the local histology, alleviate inflammation, suppress apoptosis, maintain tight junction function and decrease permeability. Interestingly, it has more of an effect on local structure preservation and inflammation inhibition in CD than in UC mice. Vitamin D blocked the increase of helper T-cell type 1 (Th1)- and helper T-cell type 17 (Th17)-related cytokines in TNBS-induced colitis. But the increase of helper T-cell type 2 (Th2)- and regulatory T cells (Treg)-related cytokines was augmented at the same time in oxazolone-induced colitis which counteracted each other. Our study helps elucidate the differential protective effects of vitamin D on CD and UC patients, as reported in literature.